2014
DOI: 10.3923/mj.2015.21.27
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Detection and Isolation of Bdellovibrio spps. from some Fresh Water Bodies in Benue State, Nigeria

Abstract: One hundred and thirty-five water samples were collected from five fresh water bodies in three locations in Benue State, Nigeria and screened for the occurrence of Bdellovibrio spp. using the double layer agar technique. E. coli, S. typhi and Shigella spp. were used as prey bacteria. All water bodies sampled had average temperatures ranges of 26-27°C. pH values ranged between 7 and 8. Total hardness values ranged between 48 and 85 mg LG 1 , while TDO values were between 5.0 and 15.3 mg LG 1. A total of 53 Bdel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Additionally, the vibroid-shaped Bdellovibrio sp. strain F16 released from the microparticle was observed under transmission electron microscope after the addition of water (Figure 3), which showed the typical morphological features of bdellovibrios [45]. Besides, it could form round plaques as described by Williams et al (1980) [46] on the double-layer agar plate after incubation for 48 h (Figure S2), which differed from bacteriophage plaques that developed within 24 h [47].…”
Section: Resultsmentioning
confidence: 92%
“…Additionally, the vibroid-shaped Bdellovibrio sp. strain F16 released from the microparticle was observed under transmission electron microscope after the addition of water (Figure 3), which showed the typical morphological features of bdellovibrios [45]. Besides, it could form round plaques as described by Williams et al (1980) [46] on the double-layer agar plate after incubation for 48 h (Figure S2), which differed from bacteriophage plaques that developed within 24 h [47].…”
Section: Resultsmentioning
confidence: 92%
“…The genus, Bdellovibrio , also abundant in the NHC, was previously isolated from the arsenic-rich hot springs of the Himalayas [ 45 ]. Furthermore, Bdellovibrio has also been found in freshwater bodies [ 46 ], polluted rivers [ 47 ], and the human gut [ 48 ]. Thus, Bdellovibrio may be introduced to the NHC owing to the anthropogenic impact on the water body.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies on BALOs in freshwater bodies have been reported in the past two decades. In a recent report, Sar et al (2015) described the isolation of 53 BALOs from freshwater systems in Nigeria using three bacteria species. The frequency of isolation of BALOs on the three prey bacteria was 79.2% on E. coli, 18.86% on S. typhi, and 1.88% on Shigella spp.…”
Section: Non-halotolerant Balos and Preymentioning
confidence: 99%